Surviving the first five years: the economic and healthcare determinants of child mortality in Sri Lanka - Vageesha Rajapakse; Ruwan Jayathilaka (Journal of Health, Population and Nutrition)
Abstract Background This study investigates the role of economic growth, healthcare investment, immunization coverage, and malnutrition in reducing under-five mortality rates (U5MR) in Sri Lanka. Understanding how these factors interact within socio-economic ecosystems is essential to formulating sustainable strategies to improve child survival outcomes. Methods This study employs multiple linear regression to analyze the statistical associations between economic growth, healthcare investment, immunization, malnutrition, and under-five mortality in Sri Lanka. Using secondary data from the World Bank and UNICEF (2000–2021), U5MR was modeled against economic growth (per capita GDP), government healthcare expenditure (GHE), immunization coverage (DTP1), and malnutrition (MLN), with significance assessed through p-values and model fit via R². Results The multiple linear regression model demonstrated strong explanatory power, accounting for 85% of the variation in under-five mortality (R² = 0.85). Economic growth and immunization coverage were negatively associated with U5MR and found to be statistically significant (p < 0.05 and p < 0.10 respectively), indicating their potential role in reducing child mortality. Malnutrition showed a strong positive association (p < 0.01), emphasizing its continued threat to child health. Although government healthcare expenditure had a negative association, it was not statistically significant, suggesting possible inefficiencies in resource utilization. Conclusion The study highlights the significant role of economic growth, healthcare expenditure, immunization coverage, and nutrition in shaping U5MR trends in Sri Lanka. The findings emphasize the need for targeted policy interventions to enhance child health outcomes and ensure sustainable progress in reducing child mortality.